1997
DOI: 10.1002/(sici)1097-4628(19970912)65:11<2257::aid-app23>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

pH sensitivity and ion sensitivity of hydrogels based on complex-forming chitosan/silk fibroin interpenetrating polymer network

Abstract: A novel natural polymer blend, namely, a semi-interpenetrating polymer network (semi-IPN) composed of crosslinked chitosan with glutaraldehyde and silk fibroin was prepared. The FTIR spectra of the semi-IPN manifested that the chitosan and silk fibroin had a strong hydrogen-bond interaction and formed an interpolymer complex. The semi-IPN showed good pH sensitivity and ion sensitivity. According to the different swelling ratios of the semi-IPN in the buffer solution with different pH values or the AlCl 3 aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 7 publications
4
40
0
Order By: Relevance
“…By blending with other natural or synthetic polymers, such as cellulose (Freddi et al, 1995) or chitosan (Chen et al, 1997), silk fibroin can be processed into films or fiber silk fibroin scaffolds for a number of tissue engineering applications in skeletal tissues like bone and ligaments, and in connective tissues like skin. Moreover, SF films, fibers and gels have been investigated in vitro with different cell (Unger et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…By blending with other natural or synthetic polymers, such as cellulose (Freddi et al, 1995) or chitosan (Chen et al, 1997), silk fibroin can be processed into films or fiber silk fibroin scaffolds for a number of tissue engineering applications in skeletal tissues like bone and ligaments, and in connective tissues like skin. Moreover, SF films, fibers and gels have been investigated in vitro with different cell (Unger et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the ability to localize phenol reaction cascades [30] and the observation that the chemomechanical properties of these films are altered by these reactions suggests the potential to engineer chitosan films to perform finely tuned actuator functions. [43][44][45][46][47] …”
Section: Discussionmentioning
confidence: 99%
“…Further, it was found that the gelation rate of hydrogel can be controlled by various factors such as calcium content, polymer concentration and gelation temperature (Chen et al, 1997). Chen et al (2011b) developed a novel natural semiinterpenetrating polymer network (semi-IPN) composed of chitosan crosslinked with glutaraldehyde and silk fibroin.…”
Section: Doxorubicin Poly[(2-ethoxy) Ethoxy Ethyl Vinyl Ether] (Poly(mentioning
confidence: 99%